2013
DOI: 10.1055/s-0033-1337944
|View full text |Cite
|
Sign up to set email alerts
|

Does Intermittent Pneumatic Leg Compression Enhance Muscle Recovery after Strenuous Eccentric Exercise?

Abstract: Intermittent pneumatic compression (IPC) has gained rapid popularity as a post-exercise recovery modality. Despite its widespread use and anecdotal claims for enhancing muscle recovery there is no scientific evidence to support its use. 10 healthy, active males performed a strenuous bout of eccentric exercise (3 sets of 100 repetitions) followed by IPC treatment or control performed immediately after exercise and at 24 and 48 h post-exercise. Muscular performance measurements were taken prior to exercise and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 18 publications
3
45
0
4
Order By: Relevance
“…A similar pattern was noted with CRP concentrations in the EPC group and we posit that the compressive stimulus may “mobilize” a greater proportion of metabolites/cellular contents in the context of sarcolemmal injury to the extracellular space. However, Cochrane and colleagues have reported similarity in CK levels when comparing an EPC subject pool to a non-treatment control group after strenuous eccentric exercise [30]. Given the quantitative and qualitative similarity in this metric, other investigators findings, and the influence of other confounding variables when analyzing serum CK levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was noted with CRP concentrations in the EPC group and we posit that the compressive stimulus may “mobilize” a greater proportion of metabolites/cellular contents in the context of sarcolemmal injury to the extracellular space. However, Cochrane and colleagues have reported similarity in CK levels when comparing an EPC subject pool to a non-treatment control group after strenuous eccentric exercise [30]. Given the quantitative and qualitative similarity in this metric, other investigators findings, and the influence of other confounding variables when analyzing serum CK levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the earlier studies demonstrated an evaluated cardioprotection effect in disease conditions [7,28,30,54], but did not refer to skeletal muscle function. This concept, based on the assumption that a tissue with some "history" of ischemic conditions eventually becomes more resistant to ischemia and its potential deleterious effects [34,39,45], obviously attracted many researchers in sports medicine and exercise science during the last decade, resulting in a reasonable number of experimental researches attempting to demonstrate beneficial effects of IPC on skeletal muscle strength [10,38], endurance [1,20] or general sports performance [23,32,33]. Based on anecdotal information, the IPC procedure was applied by South American indigenous populations before traveling long distances, e. g., to transmit information to other communities, by ligating the thighs for some time before starting to run.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Additional studies are required to evaluate the effect of an IPC machine over extended periods of time with varying degrees of exercise duration and intensity as well as recovery duration. Recently, Cochrane et al claimed the parameters used to treat muscle damage following strenuous exercise in healthy participants are likely to be very different than those used to treat pathologic conditions [17]. There must be follow-up research to explore the factors that were limited within our study.…”
Section: Discussionmentioning
confidence: 93%